Adjuvant mitotane therapy is beneficial in non-metastatic adrenocortical carcinoma at high risk of recurrence. Issue 6 (June 2019) - Calabrese, A; Basile, V; Puglisi, S; Perotti, P; Pia, A; Saba, L; Berchialla, P; Porpiglia, F; Veltri, A; Volante, M; Reimondo, G; Berruti, A; et al.
Abstract : Objective: Many patients with adrenocortical carcinoma (ACC) suffer from tumor recurrence despite radical surgery. Evidence on the post-operative use of mitotane is controversial and no predictors of response are available. We aimed to assess whether adjuvant mitotane treatment may prolong survival in patients with non-metastatic ACC following complete resection and whether ACC patients at high risk of recurrence may benefit from treatment. Design and methods: We retrospectively reviewed data from 152 non-metastatic ACC patients followed at the San Luigi Gonzaga Hospital: 100 patients were treated with adjuvant mitotane and 52 patients were left untreated following surgery. We assessed a number of potential predictive factors of recurrence and death. Mitotane effect was explored stratifying patients by staging (stage I–II vs stage III), hormone secretion (yes vs no) and Ki67 index. Results: The non-treated group had a higher risk of recurrence (HR: 2.79, 95%CI: 1.58–4.91; P  < 0.001) than mitotane-treated group, while overall survival was not significantly different between groups. Hormone secretion, elevated Weiss score and elevated Ki67 index confer a higher risk of both recurrence and death and stage III ACC of death. Adjuvant mitotane treatment reduced significantly the risk of death in patients with elevated Ki67 index ( P  = 0.005) and in patients with stage III ACC ( P  = 0.02). Conclusions: Adjuvant mitotane may prolong recurrence-free survival in radically resected ACC patients with acceptable toxicity and may also prolong overall survival in a subgroup of ACC patients at high risk of recurrence.